A novel compound heterozygous mutation in the MYO15A gene in autosomal recessive hearing loss identified by targeted massively parallel sequencing. Issue 3 (2019) - Zhu, Guangjie; Ma, dengbin; Shi, Lusen; Zhou, Han; Chen, Jie; Gao, Xia
No abstract available